Blockchain-Enabled Election Voting System - Loke, Yong Cheng; Batcha, Nowshath K; Ziz, Nik Sakinah Binti Nik Ab (Journal of Applied Technology and Innovation, 2020)
This study carried out an investigation regarding the election voting system in Malaysia. The current voting method had used the traditional paper ballot as the voting method. Many voters had no trust towards current election voting system due to the weak security and low degree of transparency. The irrecoverable equipment such as paper ballot and indelible ink used during the election also very costly since it scaled based on the number of voters growing by years. Hence a new system had been proposed which is the Blockchain-enabled election voting system. Same as the current voting procedure, the voters also need to vote at the polling station but no longer vote using the physical ballot paper but the virtual vote instead. Blockchain had been recognized for its security and transparency due to its characteristics. The voters will log in the system using the PIN number which they will be noticed by the email. This report had carried the research for the domains and similar voting system implementation to get know of the voting process flow and the challenges met to prepare developer for the development in next semester. The research will used Python as the main language to develop and the environment tools had been specified. 4D methodology will be used as the for the whole development process. Besides that, document review and questionnaire had been selected to collect the data about the election law and the expectations of the voters towards the new system. The deliverables of the system will then suit the data analysed to produce the better one.